The funus romanorum in the Aeneid: an analysis of heroic funerals of Miseno, Anchises and Palante (Circe de clásicos y modernos, 2020)
This work analyzes the importance of carrying out the funus romanorum with dignity, from the passages of the Aeneid in which the funeral honors of three important personages are shown: a) Miseno, from which the problem that it represented will be analyzed, in the Roman world, both for the living and the dead, to remain unburied and the contamination that death brings to those who have contact with the corpse; b) Anchises and the cult of their Manes and the importance that this activity possessed, not only in the Aeneid, but in all of Rome, and from which it is affirmed in this work that the cult of their Manes not only acquires a fundamental importance at the oracular, but prefigured as a principle of future Roman apotheoses; c) the funeral of Palante, which are highlighted by the pageantry with which they are made, the consideration of the finitude of the hero and the symbolic character they possess.
Keywords: Death; funeral; Roman; symbol; apotheosis